The effect of real time feedback on velocity fluctuations in steady state rowing - Lintmeijer, L. L.; Hofmijster, M. J.; Soest, A. J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Rowing performance depends on maximization of mechanical power delivered by the rower(s) and minimization of power losses (1). Fluctuations in boat velocity result in a power loss due to boat drag that is higher than the corresponding power loss (P_drag_mean) that would occur if boat velocity would be constant at its average value. For skilled athletes, it is important to get reliable feedback in order to improve performance, especially when the variability in results is small (e.g. 2). Traditional feedback methods lack the accuracy to differentiate between small variations in effects, such as power loss due to velocity fluctuations. Therefore, we developed an innovative tool to provide real-time visual and auditory feedback about this power loss, and we performed preliminary experiments to evaluate the efficacy of this feedback. Methods: An algorithm was developed to estimate boat velocity in real time from combined accelerometer data (100Hz) and GPS data (10Hz). Power loss due to fluctuations in boat velocity, averaged over each full rowing cycle, was transformed into a single numeric parameter indicating the actual average power loss to boat drag, relative to P_drag_mean. This parameter was fed back visually in real time to single scull rowers, using an android smartphone for both data processing and feedback. In addition, auditory feedback was generated using pitch mapping of the instantaneous power loss due to velocity fluctuations around the mean velocity. Results: Preliminary results suggest that access to real-time visual or visual+auditory feedback over the course of four training sessions leads to improved awareness of velocity fluctuations and a slight decrease in the associated power loss due to velocity fluctuations. Currently, we are performing a study in which the efficacy of this feedback system is compared to the efficacy of traditional feedback by a rowing coach, while controlling for stroke rate and average boat velocity. Discussion: It must be noted that optimal rowing performance is achieved when the trade-off between power generated by the rower and power loss is optimal. This implies that minimization of power loss due to velocity fluctuations is unlikely to contribute to rowing performance in itself. Indeed, the current study is the first of a series of studies in which feedback tools will be developed and evaluated for all relevant terms in the power equation for steady state rowing, ultimately supporting elite rowers to converge to the optimal trade-off between all relevant power terms.